Movement classes during aligner staging - Martins, Renato Parsekian [UNESP]; da Silva, Roberto Soares [UNESP] (Dental Press International, 2019)
Clinicians must know how aligners are produced in order to understand how they work. Besides knowing how to set up the teeth, it is of utmost importance that the orthodontist knows how the staging of the treatment is accomplished. The movements of rotation around the three axis of teeth can be classified as synergistic, stand-alone or antagonist. Each class of movement have a different difficulty level and many times require different strategies to achieve adequate correction. Synergistic movements show good predictability, while stand alone rotations generally require attachments. On the other hand, antagonist rotations not only require attachments but also need to be staged. This means that a rotation around a specific axis need to occur apart from other movements. Additionally, stand-alone and antagonistic rotations many times require auxiliary mechanics to be achieved. The present paper aims to describe each of those classes of rotations around the center of resistance and explain, with examples, how treatment strategies must occur in each of these situations.
Classes de movimentos durante o estagiamento de alinhadores
Keywords: Orthodontics; Removable orthodontic appliances; Tooth movement